The Role Of Ai-Based Personalized Marketing On Customer Trust And Online Repurchase Intention In E-Commerce - Sumarto, Siswanda H.; Sjaifudian, Hetifah; Husnah, Nuzul (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
This study examines the effect of AI-Based Personalized Marketing on Customer Trust and Online Repurchase Intention among e-commerce users in West Java, Indonesia. As artificial intelligence becomes increasingly embedded in e-commerce through personalized recommendations, targeted promotions, and behavior-based notifications, its effectiveness depends not only on relevance and usefulness but also on the ability to build customer trust. Therefore, Customer Trust is positioned as a mediating variable in this study. A quantitative explanatory approach was employed, using data collected from 220 active e-commerce users in West Java who had purchased online at least twice in the last six months and had been exposed to AI-based personalized marketing. The data were analyzed using PLS-SEM with SmartPLS 4. The results show that AI-Based Personalized Marketing positively and significantly affects Customer Trust (β = 0.516, p < 0.001) and Online Repurchase Intention (β = 0.225, p < 0.001). Customer Trust also positively and significantly affects Online Repurchase Intention (β = 0.454, p < 0.001) and partially mediates the relationship between AI-Based Personalized Marketing and Online Repurchase Intention (β = 0.234, p < 0.001). These findings highlight trust as a key mechanism linking personalization and sustainable repurchase behavior in e-commerce.